Pengaruh Pemanfaatan Multimedia Berbasis Autoplay Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPS Kelas VIII di SMP 29 Padang - Rahmi, Nur; Yeni J, Fetri; Rahmi, Ulfia; Amsal, Mutiara Felicita (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study is to reveal the effect of the use of multimedia autoplay on student learning outcomes in social studies class VIII at SMPN 29 Padang. The research method used in this study is quantitative research using the experimental method, which is to present the phenomenon as it is with its appearance, in accordance with the research frame of reference. The population in this study is all grade VIII students for the 2023/2024 Academic Year. The sample was taken using the purposive sampling technique consisting of class VIII 8 as many as 30 students as an experimental class and class VIII 9 as many as 32 students as a control class. The technique used in collecting data is the learning outcome in social studies subjects in the form of multiple choice with 30 questions. The data analysis technique of this study uses a t-test. The results showed that the average score of the experimental class that utilized autoplay-based multimedia was 78.7, which was higher than the average score of the control class that used textbooks and teaching materials, which was 60.06. Based on the results of the t-test calculation, it can be concluded that the use of autoplay-based multimedia is effective and efficient on the learning outcomes of grade VIII students in social studies subjects at SMPN 29 Padang